Prediction of oxide scale growth and thermo-mechanical stress-strain of austenitic steel and nickel-based alloy tubes in ultra-supercritical power plant / Yeo Wei Hong - Yeo, Wei Hong (2017)

(untitled)
The increasing of energy demand and aims of reducing CO2 emissions promote the future coal-fired fuel power industries to pursue for the higher steam temperatures and pressures to increase the boiler efficiency. Higher operating temperatures and pressures will increase the risk of steam-side oxidation in the boiler tubing and this could post several potential concerns such as the thickening of low thermal conductivity oxide scale can cause rapid increase in the fire-side and steam-side oxidation rates. Furthermore, the associated stresses and strains accumulation during the scale growth can cause scale exfoliation, especially when the hoop strain exceeded a value obtained from the oxide failure criteria. Austenitic steel and nickel-based alloys are often known to be the preferred choice of materials under the aggressive operation environment, thus, the oxidation behavior and thermo-mechanical stress-strain should be investigated when these materials are used for boiler tubing. To date, no literature has been reported on estimating the oxide scale growth and thermo-mechanical stress-strain of austenitic steel and nickel-based alloy tubes under the USC operation. Thus, in this research, a simple and efficient analytical solution was proposed to evaluate the temperature distribution and thermo-mechanical stress-strain of multi-layered cylinder tubes. The analytical solutions were then included into the iterative procedures for the estimation of oxide scale growth in boiler tubes. It would allow the simulation to produce more comprehensive results. The scale growth predictions were verified with actual data from power plants. Meanwhile the results obtained from the analytical thermo-mechanical solutions were compared and verified with those produced by the finite element analysis software of ANSYS. To investigate the events of the scale exfoliation during the service, an oxide scale failure model was adopted, and the parameters for determining the critical strain causing the exfoliation were proposed. Verification of the findings with the published data was provided. The evaluations of the effect of oxide scale growth and presumed exfoliation on the temperature distribution and thermo-mechanical stress-strain in the boiler tubes (austenitic steel and nickel-based alloy) were carried out. In general, based on the simulations demonstrated in the present work, the oxide scale growth rates of austenitic at steam temperatures of around 650oC seemed to be acceptable in USC operations, meanwhile those of nickel-based alloys at steam temperatures up to 750oC were found to be allowable in the operations. With regard to the potential of faster rates of oxidation, further viability studies and careful consideration on the use of nickel-based alloys for steam temperatures operations of 800oC or higher are required. It was also observed that when both steam-side/ID (inner diameter) and fireside/OD (outer diameter) scales developed on the tube, the ID scales would experience higher strain than that in the OD scales. As a result, the ID scales were more susceptible to oxide scale failure as compared to the OD scales. The research revealed that blockage due to exfoliation of steam-side scale could result in steam flow starvation in the tube thus leading to elevation of the metal temperature, and consequently causing rapid scale growth in the tube.